Dampak implementasi kurikulum merdeka belajar terhadap pembentukan karakter siswa - Feni, Nur; Nursa’ban, Eva; Supryanto, Tri (Jurnal Ilmiah Global Education, 2025)
This research aims to analyze the impact of the implementation of the Merdeka Belajar Curriculum on the character development of students, focusing on the learning process and the challenges faced in schools. The research method used is descriptive qualitative through interviews with teachers and field observations. The results show that the implementation of the Merdeka Curriculum has provided a broader space for students to be active, creative, and critical through various learning methods, such as group discussions and project-based learning. The impact is evident in the increased values of the Pancasila Student Profile, such as cooperation, independence, critical thinking, and student creativity. However, challenges are still found, including time limitations, a lack of learning facilities, and low awareness among some students in maintaining decorum and cleanliness.